Shaping of ion energy spectrum due to ionization in ion acceleration driven by an ultra-short pulse laser. (28th September 2018) - Yu, J Q; Ma, W J; Lin, C; Yan, X Q
Abstract: In the interaction between an ultra-short laser pulse and an ultra-thin film target, field ionization dominates the plasma formation. The charge and density distribution of the plasma are determined by the laser pulse and the target, and play a crucial role on the following ion acceleration process. In this paper, we study the role of ionization in laser ion acceleration with particle-in-cell simulations. The ion energy spectra in the simulations including ionization are significantly shaped comparing with those from the simulations using a pre-ionized plasma. The shaping of the ion energy spectra is robust in a wide parameter range, in term of laser temporal profile, intensity, duration and target material. This work also shows the possibility to generate quasi-monoenergetic ion beams resulted by ionization. The benchmark simulation well reproduces the narrow bandwidth ion energy spectra, the evolution of the particle number with charge state, and the leaps on the ion energy, those observed in the previous experiments. This study reveals the necessity to include ionization in modeling laser ion acceleration, and provides an approach to understand the shaping of ion energy spectra in the experiments.